Let's analyze each equation one by one to determine the number of solutions for each.
-
Equation: \( x - 7 = 7 - x \)
- Rearranging the equation: \( x + x = 7 + 7 \) leads to \( 2x = 14 \), so \( x = 7 \).
- Number of Solutions: 1
-
Equation: \( 3(x + 5) = 3x + 5 \)
- Distributing \( 3 \) on the left side gives \( 3x + 15 = 3x + 5 \).
- Subtracting \( 3x \) from both sides results in \( 15 = 5 \), which is a false statement.
- Number of Solutions: 0
-
Equation: \( 10 - x = 25 \)
- Rearranging gives \( -x = 25 - 10 \), so \( -x = 15 \) or \( x = -15 \).
- Number of Solutions: 1
-
Equation: \( 2(x + 4) = 2x + 5 + 3 \)
- Distributing \( 2 \) on the left side gives \( 2x + 8 = 2x + 8 \).
- This simplifies to \( 0 = 0 \), which is always true, meaning there are infinitely many solutions.
- Number of Solutions: Infinite
In summary:
- \( x - 7 = 7 - x \): 1 solution
- \( 3(x + 5) = 3x + 5 \): 0 solutions
- \( 10 - x = 25 \): 1 solution
- \( 2(x + 4) = 2x + 5 + 3 \): Infinite solutions